"I that is we, we that is I," perspectives on contemporary Hegel : social ontology, recognition, naturalism, and the critique of Kantian constructivism - Testa, Italo. (Critical Studies in German Idealism, 2016)
In \'I that is We, We that is I\' , an international group of philosophers explore the many facets of Hegel's formula which expresses the recognitive and social structures of human life. The book offers a guiding thread for the reconstruction of crucial motifs of contemporary thought such as the socio-ontological paradigm; the action-theoretical model in moral and social philosophy; the question of naturalism; and the reassessment of the relevance of work and power for our understanding of human life. This collection addresses the shortcomings of Kantian and constructivist normative approaches to social practices and practical rationality it involves. It sheds new light on Hegel's take on metaphysics and puts into question some presuppositions of the post-metaphysical interpretative paradigm.